Deviant peer affiliation mediates the influence of parental psychological control on adolescent aggressive behavior: The moderating effect of self-esteem. (February 2022) - Lin, Shuang; Yu, Chengfu; Chen, Jun; Sheng, Jing; Hu, Yousong; Zhong, Lin; Zhang, Yuzhi
Abstract: Although previous research indicated that parental psychological control (PPC) functions as an important risk factor for the development of aggressive behavior in adolescents; the underlying mechanisms in this association remain unclear. Using a one-year longitudinal design, the current study examined the roles of deviant peer affiliation (DPA) and self-esteem on the association between PPC and aggressive behavior. A sample of 438 adolescents ( M = 12.67 years, SD = 0.55 at T1) completed the PPC, DPA, self-esteem, and aggressive behavior assessments three times (T1, T2, and T3; six-month intervals). Structural equation modeling indicated that DPA mediated the relationship between PPC and aggressive behavior, and self-esteem moderated the mediating effect of DPA. Specifically, for adolescents with low self-esteem, PPC positively predicted DPA, ultimately increase aggressive behavior. Conversely, the indirect effects were not significant for adolescents with high self-esteem. The results highlighted the significance of identifying the mediating and moderating mechanisms between PPC and aggressive behavior. Highlights: Parental psychological control (PPC) was positively related to adolescent aggression. Deviant peer affiliation mediated the longitudinal link between PPC and adolescent aggression. Self-esteem moderated the link between PPC and deviant peer affiliation.